'Sing Psalms to the Lord with the Harp': Attitudes to Musical Instruments in Early Christianity - 680 A.D - Shirt, David (Journal of early Christian history, 2016)
The subject of this study is the assessment of any role which instrumental music might have had during the first eight centuries of Christian worship. Arguments for the absence of instrumental music in early Christian worship are commonly founded on texts which more accurately describe the attitudes of their educated, elite authors than the actuality of popular religious ritual associated with the non-elite Christian(ized) masses. Equally significant, arguments for the absence of instrumental music largely ignore life beyond the Mediterranean world. Here, in more remote locations such as ireland and Ethiopia, converts embraced Christianity and expressed it in the context of their own culture. However important the Roman Empire was, the horizons on which any assessment of musical practice is focused, must extend beyond its geographical borders. This not only involves examining a diversity of geographical locations, but a diversity of definitions regarding concepts of Christian worship. It is not only the attitudes of the elite, well aware of the disciplines of their philosophical/theological heritage, but also the attitudes of the uneducated masses, whose religious practices were not necessarily in conformity with the desires and demands of Church authority, which provide the groundwork upon which this study is built.